El sistema de distribución y la eficacia en programas de asistencia nutricional infantil. Caso Bienestarina - Colombia - Rueda Velasco, Feizar Javier; Adarme Jaimes, Wilson; Gonzalez Feliu, Jesus (Ingeniería, 2021)
Context: Food Assistance Programs (FAP) produce and distribute food to fight malnutrition on vulnerable populations. FAP distribution system allows connecting the supply with the vulnerable population demand. This research explores the links and relations between the distribution system components and the FAP’s efficacy. The research is focused on a FAP called “Bienestarina Más®” in Colombia, highly associated with childhood welfare. Method: The relations between the distribution system and program efficacy is analyzed comparing real FAP delivery data and official population statistics. The capabilities of the information systems are compared with the FAP scope using user manuals and official reports. Results: The analysis shows improvement potential in the coverage of the Colombian South-West region, gaps between offer and demand, especially when the study evaluates disaggregated data. Also, the research found a lack of coherence in the freight flows and the difference between FAP’s scope and the information systems used for user regis-ter-recognition and freight traceability. Conclusions: The research shows a lack of coordination between FAP access procedures, the population social profiles, the freight flows allocations and the scope of the information technologies. The coordination failures affect the efficacy of the program the childhood population attention.